Company Disclosure In Indonesia: Corporate Governance Practice, Ownership Structure, Competition And Total Assets - Utama, Cynthia Afriani (Asian Journal of Business and Accounting, 2012)
The purpose of this study is to investigate whether the extent of company disclosure in Indonesia is affected by external factors in addition to internal factors. Many previous studies relating to disclosure conducted in Indonesia only focused on the internal factors, e.g. corporate governance, ownership structure (blockholder) and total assets. Further, I address the possibility of non- linear relationship between ownership structure on company disclosure and also the impact of competition as an external factor to company disclosure level. This study employs Botosan Index and Herfindahl Index (HI) as a proxy for company disclosure and competition. The result shows that corporate governance practice, competition, and size have a positive influence on company disclosure leves.. When blockholder ownership is divided into three groups: low ownership (less than or equal 20%), medium ownership (between 20.1% and 50%, and high ownership (greater than 50%), I find that companies with medium blockholder ownership have a lower disclosure level than low ownership, while companies with high ownership have a higher disclosure level. Therefore, the existence of blockholder ownership ranging between 20.1% until 50% tends to yield the alignment effect whereas blockholder ownership greater than 50% tends to yield the entrenchment effect. Finally, the result also shows that leverage does not significantly impact on company disclosure. Keywords: Corporate Governance, Competition, Company Disclosure, Ownership structure